2017
DOI: 10.1002/sim.7410
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of constrained randomization for the design and analysis of group‐randomized trials with binary outcomes

Abstract: Group-randomized trials (GRTs) are randomized studies that allocate intact groups of individuals to different comparison arms. A frequent practical limitation to adopting such research designs is that only a limited number of groups may be available, and therefore, simple randomization is unable to adequately balance multiple group-level covariates between arms. Therefore, covariate-based constrained randomization was proposed as an allocation technique to achieve balance. Constrained randomization involves ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 75 publications
(149 citation statements)
references
References 56 publications
(110 reference statements)
6
143
0
Order By: Relevance
“…We consider two choices of degrees of freedom (DoF). The first DoF dates back to the work of Mancl and DeRouen 29 and equal to the number of clusters minus the number of regression parameters; this DoF has been previously used in the GEE analyses of parallel CRTs, 32 three-level CRTs, 33 crossover CRTs, 6 stepped wedge CRTs, 5,34 and shown to have test size not exceeding the nominal level. The second DoF was suggested in the PhD dissertation of Ford 35 and specifies DoF = I − 2.…”
Section: Calculations 41 | Closed-form Variance Of the Intervention mentioning
confidence: 99%
“…We consider two choices of degrees of freedom (DoF). The first DoF dates back to the work of Mancl and DeRouen 29 and equal to the number of clusters minus the number of regression parameters; this DoF has been previously used in the GEE analyses of parallel CRTs, 32 three-level CRTs, 33 crossover CRTs, 6 stepped wedge CRTs, 5,34 and shown to have test size not exceeding the nominal level. The second DoF was suggested in the PhD dissertation of Ford 35 and specifies DoF = I − 2.…”
Section: Calculations 41 | Closed-form Variance Of the Intervention mentioning
confidence: 99%
“…It is well known that randomization in individual randomized controlled trials (RCTs) balances both observed and unobserved covariates, thereby ensuring the precision and internal validity of the treatment estimate, even without accounting for important covariates. This implies that, for an RCT, a mean difference (for continuous Previous studies sought to investigate imbalance in cluster-level covariates using a continuous outcome, but few previous studies focused on individual-level covariates or evaluated binary clinical outcomes [10][11][12]. Assuming no presence of heterogeneity of treatment effect (HTE), we sought to quantify the impact of imbalance in individual-level covariates (eg, race) on the average treatment effect in CRTs for both continuous and binary outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The design is based on adjustment of baseline covariates to avoid chance imbalance. Covariate-constrained randomization [ 15 , 16 ] is the method which is used to balance for many covariates between the intervention and standard treatment arms. This method limits the risk of selection bias.…”
Section: Methodsmentioning
confidence: 99%